2016
DOI: 10.1007/s00787-016-0884-8
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety symptoms in children and adolescents diagnosed with OCD

Abstract: Health anxiety (HA) is an overlooked area in paediatric research. Little is known about the occurrence of HA symptoms in a child and adolescent psychiatric setting, and there are no age-appropriate diagnostic criteria and only limited number of assessment tools. It is therefore likely that HA is seen as part of obsessive-compulsive disorder (OCD) due to construct overlap and the diagnostic uncertainty of HA in this age group. In the present study, the extent of HA symptoms was investigated in 94 children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Recent studies show that health anxiety is commonly reported in children and adolescents diagnosed with OCD (Duholm et al., 2021; Villadsen et al., 2017). Villadsen et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies show that health anxiety is commonly reported in children and adolescents diagnosed with OCD (Duholm et al., 2021; Villadsen et al., 2017). Villadsen et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) found that 30% of a pediatric OCD sample presented with high health anxiety symptoms and that the majority (67%) of these children and adolescents were categorized with moderate to severe OCD, indicating that the presence of concurrent health anxiety was associated with greater OCD impairment. Furthermore, children with both OCD and health anxiety symptoms presented with significantly more comorbid anxiety disorders and anxiety symptoms in both studies (Duholm et al., 2021; Villadsen et al., 2017). Overall, these associations may therefore to some degree be explained by the previously mentioned substantial phenomenological overlap between health anxiety and OCD with significant cognitive and behavioral similarities involving intrusive, distressing thoughts, and related repetitive behaviors (Barsky, 1992; Deacon & Abramowitz, 2008; Starcevic, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations